Impacts of Domestic Savings on Economic Growth of Vietnam - NGUYEN, Nhung Thi Kim; NGUYEN, Hiep Huu (Asian Journal of Economic Modelling, 2017)
This paper aims to examine the short run and long run impacts of domestic savings on economic growth of Vietnam during the 1986-2015 period by using ARDL bound testing approach, while accounting for domestic investment and dependency ratio. The short run estimates show that domestic savings, domestic investment and dependency ratio do not have any impacts on economic growth. The long run estimates show that domestic savings and investment are the engines of Vietnam economic growth while dependency ratio has a negative impact on growth.